One million years of glaciation and denudation history in west Greenland - Astrid Strunk (Nature Portfolio, 2017)
Erosion rates and ice cover extent of present day fjords and summit plateau landscapes beyond the last deglaciation are virtually unknown. Here, the authors constrain the long-term denudation rates and glaciation history in west Greenland based on cosmogenic nuclides.